194 Return to work after work injury: a comparative policy effectiveness study. (1st September 2016) - Collie, Alex; Lane, Tyler; Hassani-Mahmooei, Behrooz; Thompson, Jason; McLeod, Christopher
Abstract : Background: Extended periods of time off work can have a negative impact on health. Australia has an array of state-based workers' compensation systems that seek to return injured workers to the workforce at minimal cost to society. These systems vary substantially in their design, and with respect to return to work (RTW) policy and practice. This study examined whether workers' compensation policy is an independent predictor of RTW following work injury. Methods: Comparative analyses of administrative data from eight Australian workers' compensation systems, containing 94, 675 accepted work injury claims. Logistic regression controlling for demographic, work and injury factors were used to assess whether jurisdiction of claim had an independent impact on time loss from work at 4, 13, 26, 52 and 104 weeks post injury. Results: Substantial jurisdictional differences were identified at all time points post injury, after controlling for demographic, work and injury factors. Compared to New South Wales: workers in Victoria and South Australia had significantly greater odds of being off work (receiving income benefits) at all time points; workers in Tasmania had greater odds of being back at work (off benefits) at all time points, while RTW of workers in Western Australia and Queensland improved at later time points. The magnitude of jurisdiction effects were as or more substantial than that identified for injury type, age, gender, occupation and socio-economic status. Conclusions: Workers' compensation system design has a significant and independent impact on RTW following work injury. Findings reveal the need for identification and implementation of policies and practices that promote timely and appropriate RTW.